2021
DOI: 10.46827/ejse.v7i3.3905
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Perception on the Effectiveness of Head Teachers’ Supervisory Role on Teaching and Learning of Adaptive Skills by Learners With Intellectual Disabilities

Abstract: Abstract: The purpose of this study was to explore teachers’ perception on the effectiveness of head teachers’ supervisory role on teaching and learning of adaptive skills by learners with Intellectual Disabilities (ID), Kenya. The study used Effective School Theory advanced by Lezotte. A descriptive survey design involving both qualitative and quantitative approaches was used. The target population was 227 respondents (207 learners, 5 head teachers and 15 teachers). The sample size was 124 respondents (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Most of the challenges individuals with ID face range from difficulties with personal care and household activities, to trouble with community participation and employment. For instance, a study by Ruteere (2013) on the effectiveness of teaching methods for daily-living skills to learners with intellectual disability in special units in primary schools revealed that learners with intellectual disability were not taught daily living skills effectively because teachers did not use appropriate teaching methods, strategies, or correct teaching/learning materials. It further emerged that majority of the teachers (78.0%) were not trained to teach learners with ID.…”
Section: Barriers To Independent Living For Individuals With Intellec...mentioning
confidence: 99%
“…Most of the challenges individuals with ID face range from difficulties with personal care and household activities, to trouble with community participation and employment. For instance, a study by Ruteere (2013) on the effectiveness of teaching methods for daily-living skills to learners with intellectual disability in special units in primary schools revealed that learners with intellectual disability were not taught daily living skills effectively because teachers did not use appropriate teaching methods, strategies, or correct teaching/learning materials. It further emerged that majority of the teachers (78.0%) were not trained to teach learners with ID.…”
Section: Barriers To Independent Living For Individuals With Intellec...mentioning
confidence: 99%